I knew I loved you - Savage Garden; Afanasieff, Walter; Sony Music Entertainment (New York : Sony Music Entertainment, 1999)
Contains the single taken from the album Affirmation.
CD 1 : I Knew I Loved You / (3:45).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Popular music; Songs, English